2020
DOI: 10.1021/jacs.0c11037
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Tessellations via Pillar[n]arenes-Based Exo–Wall Interactions

Abstract: Supramolecular tessellation is a newly emerging and promising area in supramolecular chemistry because of its unique structural aesthetics and potential applications. Herein, we investigate the "exo−wall" interactions of pillar[n]arenes and prepare fantastic hexagonal supramolecular tessellations based on perethylated pillar[6]arenes (EtP6) with electron-deficient molecules 1,5-difluoro-2,4-dinitrobenzene (DFN) and tetrafluoro-1,4benzoquinone (TFB). The crystal structures clearly confirm that EtP6 can form hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 71 publications
0
25
0
Order By: Relevance
“…In most of the supramolecular tessellation (tessellation at molecular level by making use of the favorable noncovalent interactions) systems, the design of vertices is a universal way to fabricate various tessellations since the symmetry element of vertex could determine the geometry superstructures of molecular tessellation 27 30 . In comparison, construction of the tessellations with polygonal macrocycles offers an alternative and effective method 31 36 . However, this method is less explored due to the lack of perfect polygonal macrocycles and the difficulty in how to achieve large-scale controllable self-assembly using the macrocycles as building blocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the supramolecular tessellation (tessellation at molecular level by making use of the favorable noncovalent interactions) systems, the design of vertices is a universal way to fabricate various tessellations since the symmetry element of vertex could determine the geometry superstructures of molecular tessellation 27 30 . In comparison, construction of the tessellations with polygonal macrocycles offers an alternative and effective method 31 36 . However, this method is less explored due to the lack of perfect polygonal macrocycles and the difficulty in how to achieve large-scale controllable self-assembly using the macrocycles as building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…1a ). Recently, Huang et al 36 constructed a new kind of supramolecular tessellations via exo-wall interactions of pillar[6]arene with hexagonal configuration (Fig. 1b ).…”
Section: Introductionmentioning
confidence: 99%
“…This is because they are easily prepared in one-step synthesis process that produces high yields, they are readily modified, and they have rich hostguest chemistry. [18][19][20][21][22][23] Several types of supramolecular polymer gels have been constructed on the basis of P[n]A. [24][25][26][27][28][29][30] Various properties and functions, such as responsiveness, [31] separation, [32] drug delivery, [33] self-healing, [13] adsorption, [34] and luminescence, [35,36] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Accordingly,c reation of novel strained p-conjugated macrocycles with organized 2D lattice superstructures through self-assembly have the potential not only to circumvent the problems in state-of-the-art artificial photosynthesis but also to influence the development of luminescent materials,p hotocatalysts,s olar cells, optical sensors,etc. [3] Recent studies have shown that tessellation of tubular cyclophanes [4] and pillararenes [5] led to formation of 2D square and honeycomb tiling patterns.Inthis context, carbon nanohoops with conjugated structures,l ike [n]cycloparaphenylenes (CPPs) [6] and p-extended (naphthalene, [7] anthracene, [8] chrysene, [9] anthanthrene, [10] hexa-peri-hexabenzocoronene, [11] fluorene, [12] benzothiadiazole, [13] thiophene [14] )C PP analogues appeared to be suitable frameworks in an attempt to mimic the light harvesting complexes.H owever,t hese distorted structures all have considerably high torsional angles (q:ca. 27-358 8)caused by CÀH/CÀHsteric interactions, resulting in less p overlaps and evident decrease in conjugation between the neighboring aromatic rings, [15,16] further hampering the face-to-face arene-arene stacking,a si so ften observed for linear arene systems [17] (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that tessellation of tubular cyclophanes [4] and pillararenes [5] led to formation of 2D square and honeycomb tiling patterns. In this context, carbon nanohoops with conjugated structures, like [ n ]cycloparaphenylenes (CPPs) [6] and π‐extended (naphthalene, [7] anthracene, [8] chrysene, [9] anthanthrene, [10] hexa‐peri‐hexabenzocoronene, [11] fluorene, [12] benzothiadiazole, [13] thiophene [14] ) CPP analogues appeared to be suitable frameworks in an attempt to mimic the light harvesting complexes.…”
Section: Introductionmentioning
confidence: 99%